Overview of anti-viral effects of probiotics via immune cells in pre-, mid- and post-SARS-CoV2 era - Kanauchi, Osamu; Low, Zhao Xuan; Jounai, Kenta; Tsuji, Ryohei; AbuBakar, Sazaly (Frontiers in Immunology, 2023)
The COVID-19 outbreak has caused significant global changes and increased public awareness of SARS-CoV-2. Substantial progress in developing vaccines, enhancing sanitation practices, and implementing various measures to combat the virus, including the utilization of probiotics has been made. This comprehensive review examined the medical impact of clinically proven probiotics on infectious diseases, considering three crucial time periods: before (pre-), during (mid-), and after (post-) COVID-19 pandemic era. This review also showed a perspective on the use of probiotics to stimulate the innate immune system and prevent infectious diseases. In pre-COVID-19 era, several probiotic strains were found to be clinically effective in addressing gastrointestinal infectious diseases, the common cold and flu. However, the mechanism by which probiotics exerted their antiviral effects remained relatively unclear during that period. Nevertheless, probiotics, Lactococcus lactis strain Plasma (LC-Plasma), and others have gained attention for their unique ability to modulate the immune system and demonstrate antiviral properties. While some probiotics have shown promise in alleviating gastrointestinal symptoms linked to COVID-19, their direct effectiveness in treating or preventing COVID-19 progression has not yet been conclusively established. As we transition into the post-COVID-19 era, the relationship between COVID-19 and plasmacytoid dendritic cells (pDCs), a vital component of the innate immune system, has been gradually elucidated. These findings are now being applied in developing novel vaccines and treatments involving interferons and in immune activation research using probiotics as adjuvants, comparable to CpG-DNA through TLR9. The role of the local innate immune system, including pDCs, as the first line of defense against viral infections has gained increasing interest. Moving forward, insight of the immune system and the crosstalk between probiotics and the innate immune system is expected to highlight the role of probiotics in adjunctive immunoregulatory therapy. In combination with drug treatments, probiotics may play a more substantial role in enhancing immune responses. The immunoregulatory approach using probiotics such as LC-Plasma, which can induce anti-infectious factors such as interferons, holds promise as a viable therapeutic and prophylactic option against viral infectious diseases due to their good safety profile and protective efficacy.